Pengaruh Psikoedukasi Terhadap Kemampuan Kognitif Keluarga Merawat Pasien Gangguan Jiwa di RSJ Prof. Dr.V.L. Ratumbuysang Minahasa - Gustin Harun; Helly Katuuk; Sri Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Psychoeducation is the provision of information and development in the form of public education as information from simple psychology or other things and can influence the psychosocial welfare of society. Family psychoeducation therapy or Family Psychoeducation is a therapy that involves the family in a treatment program by providing education through therapeutic communication. Cognitive Behavior Therapy is a combination of two approaches in psychotherapy, namely the focus in cognitive therapy is on thoughts, assumptions, beliefs, facilitating individuals to learn to recognize and change errors in thinking or irrational thoughts into rational ones. The aim of this research is to determine the effect of psychoeducation on the ability of families to care for mental disorders patients at RSJ Prof. Dr. V. L. Ratumbusang Minahasa. The research method uses the pre-Experiment Design method with a One Group Pre-Post Test approach. Samples were taken based on the number of 15 respondents using accidental sampling. Data collection uses SAP and questionnaire sheets. Next, the collected data was processed using the SPSS version 16.0 computer program and statistical tests were analyzed using the Wilcoxon test with a significance level (α=0.05). The results of research using the Wilcoxon test showed that this value was smaller than the significant value of (0.001<0.05). The results of this study showed that Ha was accepted and H0 was rejected. The conclusion in this research is that there is an influence of Psychoeducation on the Cognitive Ability of Families Caring for Mentally Disordered Patients at RSJ Prof. Dr. V. L. Ratumbuysang Minahasa. It is hoped that nurses will be able to carry out psychoeducational actions for families to improve the client's and family's abilities in caring for patients with mental disorders.